Comparative studies of genome-wide maps of nucleosomes between deletion mutants of elp3 and hos2 genes of Saccharomyces cerevisiae. - Takashi Matsumoto; Choong-Soo Yun; Hirofumi Yoshikawa; Hiromi Nishida (PLoS ONE, 2011)
In order to elucidate the influence of histone acetylation upon nucleosomal DNA length and nucleosome position, we compared nucleosome maps of the following three yeast strains; strain BY4741 (control), the elp3 (one of histone acetyltransferase genes) deletion mutant, and the hos2 (one of histone deactylase genes) deletion mutant of Saccharomyces cerevisiae. We sequenced mononucleosomal DNA fragments after treatment with micrococcal nuclease. After mapping the DNA fragments to the genome, we identified the nucleosome positions. We showed that the distributions of the nucleosomal DNA lengths of the control and the hos2 disruptant were similar. On the other hand, the distribution of the nucleosomal DNA lengths of the elp3 disruptant shifted toward shorter than that of the control. It strongly suggests that inhibition of Elp3-induced histone acetylation causes the nucleosomal DNA length reduction. Next, we compared the profiles of nucleosome mapping numbers in gene promoter regions between the control and the disruptant. We detected 24 genes with low conservation level of nucleosome positions in promoters between the control and the elp3 disruptant as well as between the control and the hos2 disruptant. It indicates that both Elp3-induced acetylation and Hos2-induced deacetylation influence the nucleosome positions in the promoters of those 24 genes. Interestingly, in 19 of the 24 genes, the profiles of nucleosome mapping numbers were similar between the two disruptants.